Estimating treatment coverage for people with substance use disorders - Degenhardt, Louisa (2017)
Funding: The authors are grateful to M. Kumvaj for her assistance with the systematic literature search. They also thank the staff of the WMHS Data Collection and Data Analysis Coordination Centres for assistance with instrumentation, fieldwork and consultation on data analysis. The WHO’s WMHS are supported by the US National Institute of Mental Health (R01 MH070884), the MacArthur Foundation, the Pfizer Foundation, the US Public Health Service (R13-MH066849, R01-MH069864 and R01 DA016558), the Fogarty International Center (R03-TW006481), the Pan American Health Organization, Eli Lilly and Company, Ortho-McNeil Pharmaceutical Inc., GlaxoSmithKline, Bristol-Myers Squibb, and Shire. The views expressed in this report are those of the authors and should not be construed to represent the views or policies of the WHO, other sponsoring organizations, agencies, or governments. This work was supported by an Australian National Health and Medical Research Council (NHMRC) project grant (no. 1081984). L. Degenhardt is supported by an NHMRC Principal Research Fellowship (no. 1041472).